The effectiveness of cooperative learning in promoting students' grammar in English / Faridah Hanum Ghazali - Ghazali, Faridah Hanum (2011)
There has been a concern in the decline of the standard of English as a second language in Malaysia. In view of this, a study was undertaken to determine the effectiveness of cooperative learning (CL) in promoting students' English, especially grammar. Students from Sekolah Menengah Kebangsaan Jalan Pasir Puteh, Ipoh, Perak were selected to undergo a series of exercises using CL approach in learning English grammar. A mixed method involving both qualitative and quantitative methodologies was employed. Initially, students were given the Pre-Test and their marks were recorded. Subsequently, the students were assigned randomly into two groups, individual learning group and CL group. The CL group was further divided into five smaller groups and they have to complete the three grammar exercises. The students either worked in groups or performed the tasks individually for three consecutive weeks. At the end of the treatment a Post-Test was administered. The results for the Pre-Test and Post-Test were compared and contrast between the cooperative and the individual learning group. At the end of the study a survey using a self-generated Questionnaire was carried out. The data collected were processed using the SPSS software version 17. In the Pre-Test, the mean score for the individual learning group [59.22] was higher than the CL [57.45]. In contrast, the Post-Test results revealed a different scenario whereby both groups obtained an increase in the mean scores. Apparently, when the scores were converted to percentages, the individual group obtained almost similar percentages of passing grades for the Pre-Test and the Post-Test [83.34 % and 83.33 % respectively]. In the CL group, the percentages of the passing grades for the Pre-Test and the Post-Test were 90.00 % and 95.00 % indicating a 5% increase. The survey was conducted by using questionnaire which elicited their perception on three aspects. The first aspect concerned the students' perception on the effectiveness of CL in promoting students' grammar in English (The results answered Research Question 1). The results showed that they agreed that CL promotes students' grammar performance judging from the average means of the four items in the Questionnaire which is 4.15 (from a Likert scale of 1 to 5). The second aspect revealed the benefits which could be acquired from implementing CL in the classroom. The Items for this section of the questionnaire obtained an average means of 3.59 (from the Likert scale of I to 5).The students perceived that CL strategy benefited them in these areas: in fostering the exchange of information and experiences, in helping weaker learners, in acquiring useful feedback and in improving communication skills (This result answered Research Question 2). The third aspect is in SECTION D which elicited the challenges that the students face in carrying out CL activities. The highest mean (3.75) was attained by Item S which discussed the participation of the members (The result answered Research Question 3). The findings of the study revealed that CL approach is effective in promoting students' grammar in English. In addition, students have an overall positive perception concerning CL because of the benefits acquired during the study despite having to deal with the challenges. Recommendations for further research on CL in the ESL classes are to expand investigations in other components of English language such as in writing or speaking skills and to extend studies to other form two classes or at all levels of the secondary school.